Ukraine’s Counter-Strategic Responses Toward Russian Propaganda and Disinformation During the War - Numadi, Katong Ragawi (Jurnal Hubungan Internasional, 2025)
Russia's full-scale invasion of Ukraine was followed by a series of propaganda and disinformation aimed at degrading the government's political power and military capabilities in dealing with the war situation. Since the conflict escalated, there has been a significant increase in the spread of Russian propaganda messages and disinformation narratives among domestic Ukrainian society. Given the importance of political support and international legitimacy for the attack on Ukraine, the spread of propaganda and fake news about Ukraine has also targeted the global public. The enormous political impact requires Ukraine to take strategic countermeasures against the domination of Russian disinformation narratives. This study aims to explain the various strategic actions taken by the Ukrainian government and community organizations to overcome the spread of Russian propaganda messages and disinformation. This research uses a qualitative approach to analyze several of Ukraine’s actions toward Russian propaganda and disinformation attacks. A literature study technique has been conducted in this research by exploring the government’s statements, previous research, online publications, and other resources to collect data related to the topic. In general, this research found that the Ukrainian government, in collaboration with civil society communities, has increased anti-propaganda and disinformation campaigns to deal with the problems domestically. Meanwhile, various diplomatic initiatives are conducted in collaboration with governments and community organizations in different countries to counter the spread of Russian disinformation in the international sphere. It is hoped that, by applying those strategic steps, Ukraine can efficiently degrade Russia's political power and information domination regarding the war situation in the global arena. Keywords: Propaganda; Disinformation; Russia; Ukraine